2018
DOI: 10.1308/rcsann.2018.0064
|View full text |Cite
|
Sign up to set email alerts
|

Refractory hypercalcaemia secondary to localised gastrointestinal stromal tumour

Abstract: Gastrointestinal stromal tumours are a rare form of intra-abdominal neoplasm derived from mesenchymal tissue, typically presenting with abdominal pain, anaemia or bleeding into the bowel or abdominal cavity. Hypercalcaemia is an unusual complication, having been documented in only seven previous patients, all of whom had advanced metastatic disease. We present a case of treatment-resistant hypercalcaemia in a patient with non-metastatic gastrointestinal stromal tumour, which resolved following excision of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This patient had localised disease, and following resection, calcium levels stabilised. In this case, there were no abnormalities in PTH, PTHrP or calcitriol, postulating a GIST mechanism independent of calcitriol and PTHrP production 11…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This patient had localised disease, and following resection, calcium levels stabilised. In this case, there were no abnormalities in PTH, PTHrP or calcitriol, postulating a GIST mechanism independent of calcitriol and PTHrP production 11…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, one of the previous cases reported indicated that their patient presented with refractory hypercalcaemia until surgical resection of their GIST 11. This patient had localised disease, and following resection, calcium levels stabilised.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations